PlasmaBlade-assisted surgical septal myectomy: technique and our experience - Garg, Pankaj; Lykins, Amy; Alomari, Mohammad; Reynolds, Jordan P.; Johnson, Elizabeth; Sareyyupoglu, Basar (Frontiers in Cardiovascular Medicine, 2024)
Background The pulsed-electron avalanche knife (PEAK) PlasmaBlade provides an atraumatic, scalpel-like cutting precision and electrocautery-like hemostasis. PlasmaBlade operates near body temperature, and its long, thin, and malleable tip can overcome the limitations of a surgical knife. In this study, we aimed to evaluate our clinical experience and histopathological outcomes of septal myectomy using PlasmaBlade. Methods Electronic medical records were reviewed for preoperative, operative, and follow-up data of the patients who underwent septal myectomy using PEAK PlasmaBlade at our institute between January 2019 and December 2022. Histopathology of the myectomy specimens was reviewed for the depth of muscle necrosis and compared with the left atrial appendage (LAA) specimen. Results Twenty-nine patients underwent septal myectomy using the PEAK PlasmaBlade. No mortality was reported. The mean age was 60.6 ± 12.5 years, and 58.6% of patients were male. Peak left ventricular outflow tract (LVOT) gradients were 40.5 ± 34.9 mmHg at rest and 56.5 ± 34.9 mmHg after provocation. Concomitant procedures performed were LAA ligation in 20 (69.0%), aortic valve replacement in 5 (17.2%), and coronary artery bypass grafting in 3 (10.3%) patients. Postoperative complications were complete heart block in one (3.4%) and ventricular septal defect in two (6.9%) patients. Both the ventricular septal defects were identified intraoperatively and repaired. Histopathology of myectomy specimens demonstrated cautery artifact limited to <50 µm depth compared to >1,000 µm with conventional electrocautery. At a mean follow-up of 8.4 ± 10.3 months, the mean LVOT gradient was 4.4 ± 5.8 mmHg at rest and 9.5 ± 3.3 mmHg after provocation. All patients were alive and in New York Heart Association class I/II. No patient developed complications or required reintervention or reoperation. Conclusion Adequate septal myectomy can be precisely and safely performed using the PEAK PlasmaBlade with minimal collateral damage.